Impact of prospective climate change on water resources and crop yields in the Indrawati basin, Nepal. (February 2015) - Palazzoli, I.; Maskey, S.; Uhlenbrook, S.; Nana, E.; Bocchiola, D.
Highlights: We study hydrology and crop yields in the Indrawati basin of Nepal. SWAT model accurately depicts hydrology and yield of maize, rice, and wheat. We investigate potential effect of climate change until 2100. Hydrological cycle may display larger floods and droughts according to some scenarios. Crop yield may be lower, and more variable according to some scenarios. Abstract: The study aimed at developing a tool to investigate the effect of prospective climate change (until 2100) on hydrology and productivity of rain-fed crops (wheat Triticum L., maize Zea Mais L., and rice Oryza L.) in the Indrawati river basin, Nepal, Himalaya. Climate scenarios from 3 climate models (GCMs), namely CCSM4, EC-Earth and ECHAM6, each one under 3 different representative concentration pathways (RCPs) were fed to Soil and Water Assessment Tool (SWAT) and hydrological fluxes and crop yields were estimated for two time windows, i.e. half century (2045–2054) and end of century (2085–2094) against control run decade (1995–2004). The results foresee considerable potential changes of hydrological fluxes (from −26% to +37% yearly, with large difference seasonally and between models and RCPs), and potential changes of crop production (−36% to +18% for wheat, −17% to +4% for maize, and −17% to +12% for rice, again with differences between models and RCPs), also in term of yearly variability, potentially affecting food security. The CCSM4T model projected larger changes in hydrology and reduction in crop yields than other models. Wheat was found to be more vulnerable than maize and rice to climate change.